Egirl11
contestada

I don't really need help but the first person to answer gets a brainlest


9a - 7a = 3a - 33 + 2a

The final answer is A = 11 but it is your job to explain why good luck

Respuesta :

Answer:

A=11

Step-by-step explanation:

You have to combine similar terms on both sides of the equation. 9a -7a equal 2a. On the other side you will do 3a+2a which equals 5a then you’ll leave -33 by itself.

2a=5a-33

You must subtract 5a from both sides of the equation which leaves you with; -3a=-33. Finally you divide both sides by -3. Which leaves you with your final answer a=11

ACCESS MORE